Literatura infantil afro-brasileira e o PNLD literário 2018: 1º ao 3º ano do ensino fundamental e a perspectiva decolonial - Britez, Kelly Pfingstag (2023)
This is a research on Afro-Brazilian children's literature from the PNLD literary collection from 2018, from the 1st to 3rd year of Elementary School and analysis of the potential of these works for a decolonial formation based on three of the selected works: Rapunzel e o Quibungo (2012), Meu crespo é de rainha (2018) e Os tesouros de Monifa (2009). To achieve this, the main objective was to analyze decolonial representations in AfroBrazilian children's literature, together with the analysis of compliance with Law 10,639/2003, which made it mandatory to include Afro-Brazilian and African culture and history in the school curriculum and ethnic-racial.discussions. First was a survey and analysis was carried out of the number of works with ethnic-racial, Afro-Brazilian and African themes in the 2018 PNLD collection, intended for 1st, 2nd and 3rd years of basic education, based on reading the synopsis of the works. Reflections were also made on the history of Afro-Brazilian children's literature. This discussion is based on Bernd (1988), Duarte (2008) and Fonseca (2006) on black and Afro-Brazilian literature. The reflections of Debus (2017) and Munanga (2003) are voices of equal importance for the dialogue on the formation of Afro-Brazilian children's literature. With regard to reflections on the 2018 PNLD Literary data collection, the information available in the PNLD collection, in the FNDE and the contributions of Adichie (2019), Ribeiro (2019) guide the reflections. It is also contextualized Afro-Brazilian and Afro-Latin American decolonial perspective. It includes reflections based on Gonzaga (2021), with regard to the historical process from a decolonial point of view in Latin America, in addition to the concepts created by the Modernity/Coloniality group, especially the concepts of Quijano (2005) and MaldonadoTorres (2020), Neto (2016) and other researchers who discuss the issue. Finally, it was analyzed the representations of characters, themes and situations were analyzed in the three works from the selected literary corpus Rapunzel e o Quibungo (2012), Meu crespo é de rainha (2018) e Os tesouros de Monifa (2009), supported by theoretical considerations about the history of Afro-Brazilian literature and the decolonial perspective. Some of the considerations point to the fact that only 5% of the literary works in the 2018 PNLD Literary, from the 1st to 3rd year collection, cover ethnic-racial, African or Afro-Brazilian culture themes and it was considered that the three analyzed works, may be contributing to a decolonial formation. Each one in its own way and in a more consistent way, the last two, as they were written by black authors and because they do not reproduce the imagery and Euro-centric standards in the representation of the characters, themes, situations involving Afro-Brazilian culture and history, they act from the perspective decolonial.